Analog filter and circuit design handbook - Williams, Arthur Bernard 1940- (McGraw-Hill Education, 2014)
"A single-source design reference providing expert guidance on analog filter and circuit design Analog Filter and Circuit Design Handbook emphasizes the operational amplifier (op-amp) as the key building block, and provides a strong foundation of understanding of how op-amps work and what their limitations are. The book contains numerous circuit examples that provide mathematical functions on analog signals in both a linear and non-linear manner. Audio applications such as audio power amplifiers and cross-over networks are included. Extensive coverage of both active and passive filters Discusses audio power amplifiers, various types of waveforms, and non-linear amplifier applications Leads you through how IC operational amplifiers work, their critical parameters, and how to properly choose the appropriate amplifier for a given application Tables help you select the proper device for your requirements; combining amplifiers made by different manufacturers into a single table saves you from having to perform extensive searches among different manufacturers' websites. Includes free downloads: Filter Solutions from Nuhertz Technologies--enables the design of Elliptic Function low-pass filters up to the tenth order ELI 1.0--allows the design of odd-order elliptic function LC low-pass filters up to a complexity of 15 nulls (transmission zeros) or the 31st order Fltrform--an EXCEL spreadsheet arranged by chapter that contains all the significant formulas to simplify some of the calculations "-- Provided by publisher.